2023
DOI: 10.1002/aic.18080
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation behavior and mixing performance of antisolvent precipitation process in an ultrasonic micromixer

Abstract: A facile and robust ultrasonic micromixer was developed to intensify antisolvent precipitation via ultrasonic cavitation. The gas supersaturation created from solventantisolvent mixing was found to be a novel driving force which facilitated the generation of cavitation bubbles (CBs). Instead of being attached on the channel wall, numerous CBs translated across the microchannel at a speed up to 1.7 m/s, inducing intense transverse flow over the cross-section. The unique cavitation behavior enabled rapid mixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…This process was recorded by using a high-speed camera (Phantom M310, Vision Research). The details of the ultrasonic reactor are available in our previous research . In continuous crystallization, it is difficult to distinguish the nucleation and crystal growth processes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This process was recorded by using a high-speed camera (Phantom M310, Vision Research). The details of the ultrasonic reactor are available in our previous research . In continuous crystallization, it is difficult to distinguish the nucleation and crystal growth processes.…”
Section: Resultsmentioning
confidence: 99%
“…This benefit originated from the reduced mixing time between the solvent and antisolvent. Liu et al 39 found that the mixing time of ethanol and water could be shortened from 130 to 50 ms as the ultrasonic power increased from 5 to 30 W. The phenomenon of narrow particle size distribution resulting from flash mixing has been widely reported in various fields, such as precipitation, crystallization, and material synthesis. 46−48 Under the experimental conditions, the ASA crystal size varied in the range of 12.2−40.1 μm, which was smaller than that obtained in conventional equipment.…”
Section: Effect Of Operating Parameters On Continuous Crystallizationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Ostwald–Freundlich equation, decreasing the particle size of organic materials further to the nanorange has exhibited higher solubility in poor solvents, enabling the applications of high-performance small molecules as ink materials for printing processes in optoelectronic devices. The solubility of materials in various solvents serves as the basis for the solvent–antisolvent method, which is the most straightforward and commonly used approach for preparing nanoparticles. …”
Section: Introductionmentioning
confidence: 99%